Au/TiO2 Reusable Photocatalysts for Dye Degradation - Silija Padikkaparambil; Binitha Narayanan; Zahira Yaakob; Suraja Viswanathan; Siti Masrinda Tasirin (International Journal of Photoenergy)
Nanogold doped TiO2 catalysts are synthesized, and their application in the photodegradation of dye pollutants is studied. The materials are characterized using different analytical techniques such as X-ray diffraction, transmission electron microscopy, UV-visible diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy. The results revealed the strong interaction between the metallic gold nanoparticles and the anatase TiO2 support. Au doped systems showed very good photoactivity in the degradation of dye pollutants under UV irradiation as well as in sunlight. A simple mechanism is proposed for explaining the excellent photoactivity of the systems. The reusability studies of the photocatalysts exhibited more than 98% degradation of the dye even after 10 repeated cycles.